(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the safety profile of laparoscopic hydrodissection in empyema of gallbladder. Study Design: Experimental study. Place and Duration of Study: This study was conducted at the Department of Surgery at Idris Teaching Hospital Sialkot from June 2014 to July 2016. Materials and Methods: One hundred and fifty patients of empyema of gallbladder were included in this study. All the patients were diagnosed with clinical, sonological and biochemical evidence of cholelithiasis with empyema were included in the study regardless of age and gender. Laproscopic hydrodissection was done by standard 4- port technique of empyema of gallbladder was used in all cases. In this technique the adhesions of empyemic gallbladder were removed by throwing water with pressure instead of using scalpel knife in all of the 150 cases. The charts were reviewed, and age, sex, family history of the empyema of gallbladder, date of surgery, surgery type, duration of surgery, post operative complications, stay in the hospital, were recorded. Patients follow up is also recorded. The results were analyzed on SPSS version 10. A well informed written consent was taken from each patient prior to surgery. Results: In our study the incidence of empyema of gallbladder disease was found maximum at the age of 30-35 years (58%) 87 cases and minimum at the age of 46-50 years (1.3%) 02 cases. Empyema of gallbladder disease was (59.3%) 89 cases in females as compared to male (40.7%) 61 cases. The disease was (42%-47.3%) 63-71 cases in middle and high gentry class as compared to low socio economic status (10.7%) 16 cases. The urban Population had (64.7%) 97 cases as compared to rural area (35.3%) 53 cases. In our study the incidence of the disease was (62%) 93 cases from diabetic patients as compared to non diabetic patients (38%) 57 cases.Fatty people had (79.3%) 119 cases of empyema gallbladder as compared to non fatty patients (20.7%) 31 cases. It was also observed that empyema of gallbladder was higher (59.3%) 89 cases in people taking fast food as compared to patients taking simple food (40.7%) 61 cases. Majority of the patients were operated between 65-95 minutes. The overall rate of post operative complications was (20%) 30 cases in successfully completed laparoscopic hydro dissection. Majority of the patients (80%) 120 cases with successful laparoscopic hydro dissection were discharged within 48-96 hours. In (10.5%) 7 patients, the stay in the hospital was extended 5-7 days. Conclusion: Laparoscopic hydro dissection of empyema of gallbladder can be performed keeping in mind a slightly increased risk of complications even in the best hands. However the experience of the surgeon plays a key role in the overall outcome.